2018
DOI: 10.1245/s10434-018-6569-4
|View full text |Cite
|
Sign up to set email alerts
|

Positive Nipple Margin After Nipple-Sparing Mastectomy: An Alternative and Oncologically Safe Approach to Preserving the Nipple–Areolar Complex

Abstract: Management of positive nipple margin after NSM with subareolar shave biopsy is a safe alternative to preserve the NAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Eleven patients (34.4%) were treated with subareolar shave biopsies to achieve negative margins. Final pathologies after shave biopsy did not reveal residual disease, and these patients did not develop necrosis of the NAC with no recurrence at a mean follow-up of 3.2 years; thus, the study writers concluded that subareolar shave biopsy is a safe alternative to preserving the NAC 15 …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Eleven patients (34.4%) were treated with subareolar shave biopsies to achieve negative margins. Final pathologies after shave biopsy did not reveal residual disease, and these patients did not develop necrosis of the NAC with no recurrence at a mean follow-up of 3.2 years; thus, the study writers concluded that subareolar shave biopsy is a safe alternative to preserving the NAC 15 …”
Section: Discussionmentioning
confidence: 80%
“…Final pathologies after shave biopsy did not reveal residual disease, and these patients did not develop necrosis of the NAC with no recurrence at a mean follow-up of 3.2 years; thus, the study writers concluded that subareolar shave biopsy is a safe alternative to preserving the NAC. 15 de Alcantara Filho et al 14 reported a 3.1% nipple positivity rate after NSM, with 2.3% being invasive carcinoma. Jensen et al 16 reported a rate of 15% of NSMs having invasive carcinoma on subareolar frozen tissue biopsy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, our study suggests that NSM is oncologically safe even when a patient's TND is < 2.0 cm. With the increased rate of NSM use in breast cancer, several studies have compared the oncologic safety profile of this technique with that of others [1617]. Gerber et al [1] reported no significant differences in complications between NSM, SSM, and modified radical mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of patients choose breast-conserving surgery, which could lead to more positive incision margins during the operation. [8][9][10] Therefore, the positive incision margin during operation has attracted increased attention.…”
Section: Introductionmentioning
confidence: 99%